2020
DOI: 10.1038/s41427-020-00270-z
|View full text |Cite
|
Sign up to set email alerts
|

High-density Néel-type magnetic skyrmion phase stabilized at high temperature

Abstract: The discovery of a thermally stable, high-density magnetic skyrmion phase is a key prerequisite for realizing practical skyrmionic memory devices. In contrast to the typical low-density Néel-type skyrmions observed in technologically viable multilayer systems, with Lorentz transmission electron microscopy, we report the discovery of a high-density homochiral Néel-type skyrmion phase in magnetic multilayer structures that is stable at high temperatures up to 733 K (≈460 °C). Micromagnetic simulations reveal tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The isolated skyrmion in a perpendicularly magnetized system is stabilized only when several material parameters, such as the perpendicular magnetic anisotropy (PMA), the magnetic dipole interaction (μ 0 M S 2 ), and the Dzyaloshinskii–Moriya interaction (DMI), meet a particular ratio. , In some studies, a complex multilayer structure with more than ten repeated numbers was adopted to enhance μ 0 M S 2 , ,, or extremely fine interface engineering was used to adjust PMA. , Moreover, even if an optimized material to stabilize a Neel-type skyrmion is obtained, deterministic skyrmion generation is also tricky. Previous works reported the generation of isolated skyrmions using an external magnetic field, ,− spin-polarized electric current, , or thermal energy. However, the reported approaches are accompanied by a complicated patterning process to induce nonuniform spin-torque or a specific device geometry, laser, or heating holder to inject localized heat. , For example, while Woo et al reported reliable current-induced generation or annihilation of an isolated magnetic skyrmion, the underlying mechanism is based on unintended defects. As another example, Finizio et al presented a creative device structure that can nucleate and delete an isolated magnetic skyrmion using an electrical signal, but the device geometry is quite complicated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The isolated skyrmion in a perpendicularly magnetized system is stabilized only when several material parameters, such as the perpendicular magnetic anisotropy (PMA), the magnetic dipole interaction (μ 0 M S 2 ), and the Dzyaloshinskii–Moriya interaction (DMI), meet a particular ratio. , In some studies, a complex multilayer structure with more than ten repeated numbers was adopted to enhance μ 0 M S 2 , ,, or extremely fine interface engineering was used to adjust PMA. , Moreover, even if an optimized material to stabilize a Neel-type skyrmion is obtained, deterministic skyrmion generation is also tricky. Previous works reported the generation of isolated skyrmions using an external magnetic field, ,− spin-polarized electric current, , or thermal energy. However, the reported approaches are accompanied by a complicated patterning process to induce nonuniform spin-torque or a specific device geometry, laser, or heating holder to inject localized heat. , For example, while Woo et al reported reliable current-induced generation or annihilation of an isolated magnetic skyrmion, the underlying mechanism is based on unintended defects. As another example, Finizio et al presented a creative device structure that can nucleate and delete an isolated magnetic skyrmion using an electrical signal, but the device geometry is quite complicated.…”
mentioning
confidence: 99%
“…Previous works reported the generation of isolated skyrmions using an external magnetic field, 36 , 38 − 40 spin-polarized electric current, 8 , 34 or thermal energy. 41 43 However, the reported approaches are accompanied by a complicated patterning process to induce nonuniform spin-torque 9 or a specific device geometry, laser, or heating holder to inject localized heat. 41 , 42 For example, while Woo et al 44 reported reliable current-induced generation or annihilation of an isolated magnetic skyrmion, the underlying mechanism is based on unintended defects.…”
mentioning
confidence: 99%
“…In these materials, the competition between the Dzyaloshinskii-Moriya interaction (DMI) and the exchange interaction plays a significant role in stabilizing the skyrmion spin texture. Skyrmions have also been observed in multilayer thin films that in general host interfacial DMI [10][11][12]. In recent times, skyrmion like whirling spin textures with various topological numbers have been found in certain centrosymmetric magnets that exhibit uniaxial magnetocrystalline anisotropy (UMA) [13-15, 17-20, 33].…”
Section: Introductionmentioning
confidence: 99%
“…Here we study Néel skyrmion lattices in Fe 3 GeTe 2 (FGT), a van der Waals (vdW) material that is ferromagnetic down to monolayer thickness and displays signatures that suggest enhanced electronic correlations. FGT is easily exfoliated and an appealing candidate for interfacing topologically protected magnetic spin structures with superconductors, topological insulators, , or magnonic materials. , The skyrmions observed in FGT are of particular interest as, unlike in conventional metallic multilayers, the skyrmion size is strongly dependent on temperature, thus forcing the lattice to adapt and realign as the temperature is changed. By examining the order of Néel skyrmion lattices in response to varying temperature and magnetic field, we gain insight into how skyrmions interact with each other, are created and destroyed, and how the lattice itself evolves as a collection of dynamic skyrmions.…”
mentioning
confidence: 99%